Swiss Architectural Origins, Le Corbusier, and the Pātaka of Lake Horowhenua (1845) - Wood, Peter (Architectural History Aotearoa, 2014)
In April, 1845, the Rev. Richard Taylor passed through the area of the North Island now marked by the town of Levin. At this time, he described Lake Horowhenua as being of singular appearance for the small storehouses built over the water on poles. As was his predilection, Taylor made a drawing of the lake huts, a version of which was belatedly included in the second edition of his most important literary contribution, Te Ika-a-Māui (1870). This image would have remained as little more than a questionable curiosity was it not for Messrs Black Bros who, in the course of exploring the lake bed for Māori artefacts in 1932, legitimised Taylor's observation with their discovery of the submerged architectural remains of an aquatic hut. Nonetheless, almost a century after Taylor's original diary entry, GL Adkin, writing for The Journal of the Polynesian Society, lamented the neglect shown toward these remarkable structures, and which he cited as just one example of the "tantalising gaps" in the recorded history of Māori custom and culture. Sadly, it is well beyond the scope of this research to properly redress the historical neglect shown toward lake pātaka. What I do wish to do is to link these structures to an event on the shores of the Lake of Zurich, Switzerland, when Dr Ferdinand Keller noticed some half-submerged piles in 1854. Upon these remains Keller made a great, if erroneous, case for primitive "pile-work habitations" in the Swiss lakes. The impact of this argument cannot be understated. It became the privileged model for architectural origins in the German and French parts of Switzerland, and by the 1890s it was a part of standard teaching texts in Swiss schools, where it was firmly inculcated into the curriculum at the time that Charles Edouard Jeanneret was a child. This in turn has led Vogt to suggest that, in Keller's "dwellings on the water," Le Corbusier found a Primitive Hut typology that underpinned all his architectural thinking, and which is made most explicit in his principled use of piloti. What makes this all the more involved is that Keller, in searching for examples to visualise the construction of the Swiss lake dwellings, turned to the Pacific (which he categorised as at a developmental stage of architectural evolution akin to early Europe). In this paper I identify the exact etching by Louis Auguste de Sainson that Keller took for direct influence. The problem, however, is that de Sainson depicted a conventional whare built on land, and Keller transposed it to the water. So we have on the one side of this paper an authentic lake whare that is all but forgotten, and a famed European lake-hut that is all but Māori, and between the two is the figure of Le Corbusier who may or may not have unknowingly based one on his major innovations on influences found in the pātaka of Lake Horowhenua.